Evaluation types of exterior walls to reconstruct Iran earthquake areas (Ahar Heris Varzeqan) by using AHP and fuzzy methods - Hosseini, Seyed Teimor; Lale Arefi, Shahin; Bitarafan, Mahdi; Abazarlou, Sajjad; Zavadskas, Edmundas Kazimieras (International Journal of Strategic Property Management, 2016)
Two earthquakes of magnitude 6.1mb occurred at the Ahar and around 16000 residential buildings were destroyed. one of the conspicuous issues in the earthquake is property management to reconstruct and confront the crisis. in this regard, since the most damage inflicted on the buildings occurs in the exterior walls, therefore, the most financial resources must be spent on reconstructing this part of damaged buildings. Thus, this paper was conducted in order to reduce expenditure and increase the resistance of the walls. The urban fabric of the area didn’t sustain much damage and only the exterior walls of the buildings were collapsed. Thus, the main aim of this article is to study different types of exterior walls for renewal and reconstruction of buildings in earthquake area. To approach this aim, using group decision-making method. This paper presents the comparison of FUZZY and AHP. in this regard, this research is centralized on types of exterior walls to reconstruct iran earthquake areas (Ahar, Heris, Varzeqan). five main methods have been chosen by asking experts in the related fields and to evaluate and select the best of exterior walls. finally 3D panel wall was selected as the optimal wall for reconstruction of earthquake area.